Is REDD+ effective, efficient, and equitable? Learning from a REDD+ project in Northern Cambodia. Issue 83 (July 2017) - Nathan, Iben; Pasgaard, Maya
Highlights: We develop a conceptual framework for effectiveness, efficiency and equity in REDD+. The paper contains a case study of the Oddar Meanchey REDD+ project. Effectiveness and efficiency in REDD+ can only be understood in relative terms. REDD+ equity strategies depend on clear definitions of subjects of equity. There is tension between the neoliberal project and environmental, social concerns. Abstract: REDD+ is a global scale climate change mitigation program aiming at creating financial values for carbon stored in forests. According to the proponents, REDD+ is an effective, efficient, and equitable mechanism for reducing emissions from deforestation and forest degradation. Some scholars question this assumption, and some call for further analysis to understand how REDD+ can contribute to economic, environmental, and social goals, and what are the synergies and trade-offs between them. The purpose of this paper is to contribute to the debate about whether REDD+ projects can be brought to accommodate economic (efficiency), environmental (effectiveness), and social (equity) concerns at the same time by drawing on own field results from a REDD+ project in Cambodia. The paper follows three tracks. The first is to develop and explain the conceptual and analytical framework for our empirical investigations. The second is to explain the field results. The third track is to discuss what general lessons can be learnt. Our case illustrates some of the mechanisms that are likely to work against the willingness and ability of REDD+ projects to ensure local people's net-gains, and the risk that effectiveness and equity will suffer if REDD+ projects rely solely on the private market. Our case thus indicates a tension between the objectives of creating financial value from carbon stored in trees through the private market, and environmental and social equity concerns. However, we call for more comparative studies of REDD+ projects, and hope our conceptual framework can assist such studies.